Factors affecting the application of strategic management accounting in Vietnamese enterprises (International Journal of Management and Sustainability, 2024)
This study aims to provide more in-depth information on the factors influencing the application of strategic management accounting in Vietnamese enterprises. The study uses questionnaire surveys to collect primary data to test the hypotheses in the proposed research model about factors affecting the application of strategic management accounting in Vietnamese enterprises. The survey was conducted using a non-probability sampling method with 64 enterprises; 225 valid survey forms were collected using SPSS 25.0. The analysis includes variable descriptive statistics, scale reliability testing, exploratory factor analysis, multivariate regression analysis, and evaluation of regression assumptions. We used a multivariate regression method to analyze the data. The results confirm the acceptance of the hypotheses, demonstrating a significant influence of the model’s factors on the applications of strategic management accounting. Enterprise size, competition levels, business strategy development, decentralization, technology level, and accounting participation positively impact the application of strategic management accounting in enterprises. In particular, the level of competition is the most vital factor motivating Vietnamese businesses to apply strategic management accounting. The results are empirical evidence to help managers better understand the practice of applying management strategic accounting to make reasonable decisions to practice strategic management accounting and have effective performance. Furthermore, this study suggests more profound research directions aimed at promoting the application of strategic management accounting in Vietnamese enterprises.